The New Silk Road: Seeking Opportunities for Polish Exports in the Chinese Market - Ewa Cieślik (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The paper presents preliminary studies related to the problems of the New Silk Road and its influence on the Polish economy. The aim of the report is to define tendencies in the trade exchange between Poland and China and to evaluate the capacity of Polish exports to the Chinese market. The paper tries to answer the question whether the contemporary structure of Polish exports to the Chinese market allows for the full use of the potential of the Middle Kingdom market. In the study, the indicative trade potential was used.